"Uncle Jack Forward" - Rorke Family (1882)
John ''Jack'' Bemister Forward. John ''Jack'' Bemister Forward (1864-1934), youngest son of Captain Mark William and Mary (Bemister) Forward, was born on 15 December 1864. His siblings included Anne Charlotte ''Annie'' (Forward) Boone, Georgina Eliza ''George'' (Forward) Samways and Ernest Edward Forward. He married a woman named Mary and had two sons, Victor and Sandford. He died on 29 December 1934. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.